Microbiology Learning Based life Skills Education of Student In TADRIS Biology PRODI FATIK IAIN Kendari Through the Contextual Teaching and Learning Approach - Rosmini Rosmini; Badrianti Badrianti (International Journal of Transdisciplinary Knowledge, 2021)
This study aims to (1) examine the life skills of students of Tadris Biology PRODI, FATIK IAIN Kendari through Microbiology learning based on Life Skills Education using the CTL Approach, (2) examining the attitudes of Tadris Biology PRODI, FATIK IAIN Kendari after learning Microbiology Based on Life Skills Education with the CTL approach. The research sample was all students of the Tadris Biology PRODI FATIK IAIN Kendari in the fifth semester of the 2018/2019 academic year totaling 32 students. The results showed that the life skills of students of the Tadris Biology PRODI at FATIK IAIN Kendari in the fifth semester of the 2018/2019 academic year through learning Microbiology with the CTL approach, all students achieved life skills competence with an average score of 8.93. Based on the results of the questionnaire, students' attitudes showed a positive attitude, meaning that students in general (85.91%) agreed to microbiology learning based on life skills education with the Cotextual Teaching and Learning Approach. .